The Impact of Providing Islamic Spiritual Extracurriculars on Student Character Development - Firdaus; M A Jati Purnomo; M Subagus; taufiq, muhammad (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research discusses the impact of spiritual extracurricular activities on students' character development. The research objective was to determine the effect of spiritual extracurricular activities on the character development of spiritual members inside and outside of school. This research uses descriptive quantitative research with random sampling techniques or data collection. The population is the academic community of SMK N 1 Jambi, totaling approximately 200 students, and the sample is 36 students. Based on the results of research and discussion, the impact of spiritual extracurricular activities at SMK N 1 Jambi on the formation of student character plays a very important role. It can be concluded that children who participate in spiritual extracurricular activities are believed to have had an impact on their activities at school and at home, both with teachers, friends and with their parents, to become more independent, obedient and responsible where Islamic spiritual extracurricular activities take the form of coaching. the physical and spiritual. such as accompaniment, nights building faith and purity, riyadhah or sports, book review, cleaning mosques, Islamic boarding schools, and other activities to support this. So that from these activities and supported by a good Islamic spiritual environment, good character is formed towards teachers, parents and friends.